Hubungan Gagal Ginjal Kronik Tingkat 4 Dan 5 Dengan Kejadian Dislipidemia Pada Pasien Gagal Ginjal Kronik Di Rumah Sakit Umum Pusat Fatmawati Periode Tahun 2016 - Dimas Farhan Wibawanto; Salman Paris; Maria Selvester Thadeus (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2018)
Dyslipidemia is a common complication of chronic kidney disease. Dyslipidemia itself is a common risk for a cardiovascular disease, which is the leading cause of death in chronic kidney disease. This study aims to identify the relationship of chronic kidney disease stage 4 and 5 with the incidence of dyslipidemia at Fatmawati General Hospital in the period of 2016. Design cross-sectional with simple random sampling technique. Data were collected by looking at the patient's medical records. Respondents are 80 people. The study population were all patients diagnosed with chronic kidney disease at Fatmawati Central General Hospital in 2016. The results showed that most chronic kidney disease stage 4 has normal level of low density lipoprotein as many 22 people (73.33%) while at stage 5 most have high level of low density lipoprotein high as many 36 people (72%). High density lipoprotein obtained in patients with chronic kidney disease stage 4 mostly had normal level as many 20 people (66.67%) for stage 5 mostly had low level as many 33 people (66%). Mean lipid values of triglyceride X̄ = 152,36, high density lipoprotein X̄ = 39,36 and low density lipoprotein X̄ = 145,01. Result of bivariate analysis with chi square test showed significant relationship of chronic kidney disease stage 4 and 5 with incidence of dyslipidemia (p = 0,002).